Derepression of DNA damage-regulated genes requires yeast TAF(II)s - Li, Bing (Oxford University Press, 2000)
The general transcription factor TFIID and its individual subunits (TAF(II)s) have been the focus of many studies, yet their functions in vivo are not well established. Here we characterize the requirement of yeast TAF(II)s for the derepression of the ribonucleotide reductase (RNR) genes. Promoter mapping studies revealed that the upstream repressing sequences, the damage-responsive elements (DREs), rendered these genes dependent upon TAF(II)s. DREs are the binding sites for the sequence-specific DNA binding-protein Crt1 that represses transcription by recruiting the Ssn6–Tup1 co-repressor complex to the promoter. We demonstrate that deletion of SSN6, TUP1 or CRT1 alleviated the TAF(II) dependence of the RNR genes, indicating that TAF(II) dependence requires the co-repressor complex. Furthermore, we provide evidence that Crt1 specifies the TAF(II) dependence of these genes. Our studies show that TFIID interacts with the repression domain of Crt1, suggesting that the derepression mechanism involves an antagonism between TFIID and the co-repressor complex. Our results indicate that yeast TAF(II)s have other functions in addition to core promoter selectivity, and describe a novel activity: the derepression of promoters.